2012
DOI: 10.1007/s11748-012-0158-4
|View full text |Cite
|
Sign up to set email alerts
|

Nonanastomotic rupture of thoracic aortic Dacron graft treated by endovascular stent graft placement

Abstract: A 61-year-old man had a Stanford type A acute aortic dissection, and the total aortic arch was replaced with 22-mm knitted Dacron graft in 1996. In 2006, he underwent mitral valve replacement and tricuspid valve repair due to severe mitral and tricuspid valve regurgitation. Although preoperative computed tomography (CT) scan suggested pseudoaneurysm around the Dacron graft replaced with aortic arch, it could not be repaired concomitantly. Four months later, in view of the technical difficulties of an open surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Composite synthetic/natural matrix-covered stent-grafts may be promising for prolonging stent-graft patency.Synthetic vascular grafts are widely used in surgical and/or minimally invasive interventional therapeutic procedure to treat vascular diseases, such as coarctation of the aorta, aneurysm, arteriovenous fistula, dissection, iatrogenic vascular perforation, traumatic injury, and hemodialysis access 1,2 . Commercially available synthetic stent-grafts composed of expanded polytetrafluoroethylene (e-PTFE), polyethylene terephthalate (PET) and polyurethane (PU) are characterized by poor endothelialization, high modulus, and low compliance, leading to thrombosis and intimal hyperplasia [3][4][5] . Therefore, rapid endothelialization, good mechanical properties, thromboresistivity and biocompatibility are key to preserving the long-term patency of stent-grafts 6,7 .…”
mentioning
confidence: 99%
“…Composite synthetic/natural matrix-covered stent-grafts may be promising for prolonging stent-graft patency.Synthetic vascular grafts are widely used in surgical and/or minimally invasive interventional therapeutic procedure to treat vascular diseases, such as coarctation of the aorta, aneurysm, arteriovenous fistula, dissection, iatrogenic vascular perforation, traumatic injury, and hemodialysis access 1,2 . Commercially available synthetic stent-grafts composed of expanded polytetrafluoroethylene (e-PTFE), polyethylene terephthalate (PET) and polyurethane (PU) are characterized by poor endothelialization, high modulus, and low compliance, leading to thrombosis and intimal hyperplasia [3][4][5] . Therefore, rapid endothelialization, good mechanical properties, thromboresistivity and biocompatibility are key to preserving the long-term patency of stent-grafts 6,7 .…”
mentioning
confidence: 99%
“…The use of an aortic endograft in non-anastomotic aortic Dacron graft failure including rupture or localized graft aneurysm formation has been reported by several authors. Yamaguchi et al [3] reported the use of a Gore TAG endograft to treat a non-anastomotic thoracic prosthetic pseudoaneurysm in a patient who underwent aortic arch replacement with a knitted Dacron graft for a type A dissection many years ago. Similarly, Lee et al [4] documented a case of successful use of a thoracic endoprosthesis to fix a Dacron graft rupture in the descending aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Full heparinization for CPB enabled us to detect a small bleeding and to confirm hemostasis after the repair, although an urgent start of CPB was not required in the present case. Endovascular options such as thoracic endovascular aortic repair are also possible if anatomically they are available [ 6 ]. We chose resternotomy because the bleeding point could not be detected by aortography.…”
Section: Discussionmentioning
confidence: 99%